LAPISAN-LAPISAN ILMU HUKUM DALAM MEREKONTRUKSI ILMU HUKUM - Ni Luh Sri Mahendra Dewi (Widyasrama, 2022)
Science is part of knowledge, knowledge of science. Knowledge (Knowladge): information about an event that has not been verified. An orientation regarding what law is, which of course will be conceptually examined from the early history of the creation of science, then intended for the benefit of mankind as much as possible for the common good and in a legal perspective is to realize certainty, benefit and justice. law, becomes the basic concept of the formation of rules or norms or regulations that are formed through legal standards and legal principles that become elements in law. Standards, principles, elements of law essentially become a foundation in reconstructing legal science. The scientific nature of legal science can be viewed from the point of philosophy of science and legal theory. The definition of legal theory states that legal science has a distinctive character (sui generis), namely its non-active nature. The formation of laws and regulations and how the implications of their application in society are in accordance with reality (das sollen das sein) so that legal science is absolute as a science while still respecting the character of legal science with the peculiarities inherent in legal science. Science that meets the elements of science and the attainment of reasoning knowledge so that at the time of doctoral academics, theory can be in the form of a new finding, an unexplored finding (Novelty). In a broad sense, legal theory can be explained through how the law is viewed, how the science of law is formed, and how the reconstruction of the science of law. For this reason, reconstructing the law in science becomes fundamental and a renewal in a science. The purpose of studying law, both the principles, theories and concepts contained therein, becomes the essence of how the development of law, how one thinks about the law of all time, legal position in society and of course the nature of scientific characteristics rather than law that will be attached and become a legal system and method of law itself. Approach to Legal Studies as a Systematic Approach to Legal Studies in Legal Construction, Layers of Legal Studies as a Basis for Construction of Legal Studies, Legal Studies Study Methods and the conclusions of this research are 1. The distinctive scientific character inherent in legal science, intellectually viewed by legal colleagues interpreted as a sui generis character; which means the personality of legal science, consisting of: normative, applied and prescriptive. 2. Elements of Philosophy can provide a reasoning of the nature of a science, where philosophy in the science of law will be described from the pillars of the legal principles contained therein and the right theory that can synthesize knowledge from the science of law. Legal theory should fulfill the scientific elements and the attainment of reasoning knowledge so that at the time of the doctoral academic, the theory can be in the form of a new finding, an unexplored finding (Novelty). 3. In a broad sense, legal theory can be described through how the law is viewed, how the science of law is formed, and how the reconstruction of the science of law. For this reason, reconstructing the law in science becomes fundamental and a renewal in a science. The purpose of studying law, both the principles, theories and concepts contained therein, becomes the essence of how the development of law, how one thinks about the law of all time, legal position in society and of course the nature of scientific characteristics rather than law that will be attached and become a legal system and method of law itself. Then the layer of legal science can be classified into a fundamental pillar in reconstructing legal science. Layers of legal science include: Philosophy of Law, Legal Theory, Legal Dogmatics, Legal Practice, Sociology or Legal Anthropology.